Integrated North Sea grids: The costs, the benefits and their distribution between countries. (February 2017) - Konstantelos, Ioannis; Pudjianto, Danny; Strbac, Goran; De Decker, Jan; Joseph, Pieter; Flament, Aurore; Kreutzkamp, Paul; Genoese, Fabio; Rehfeldt, Leif; Wallasch, Anna-Kathrin; Gerdes, Gerhard; Jafar, Muhammad; et al.
Abstract: A large number of offshore wind farms and interconnectors are expected to be constructed in the North Sea region over the coming decades, creating substantial opportunities for the deployment of integrated network solutions. Creating interconnected offshore grids that combine cross-border links and connections of offshore plants to shore offers multiple economic and environmental advantages for Europe's energy system. However, despite evidence that integrated solutions can be more beneficial than traditional radial connection practices, no such projects have been deployed yet. In this paper we quantify costs and benefits of integrated projects and investigate to which extent the cost-benefit sharing mechanism between participating countries can impede or encourage the development of integrated projects. Three concrete interconnection case studies in the North Sea area are analysed in detail using a national-level power system model. Model outputs are used to compute the net benefit of all involved stakeholders under different allocation schemes. Given the asymmetric distribution of costs and benefits, we recommend to consistently apply the Positive Net Benefit Differential mechanism as a starting point for negotiations on the financial closure of investments in integrated offshore infrastructure. Highlights: Three North Sea offshore gird case studies are analysed. They are shown to have substantial net benefit over non-integrated network designs. Asymmetric net benefit sharing between countries is shown to be a barrier. Positive Net Benefit Differential method alleviates asymmetric benefits.